THE EFFECT OF INPUT SPACING ON EFL LEARNERS' VOCABULARY KNOWLEDGE - Mohammad Taghi Farvardin; Ashraf Bagherian Sararoodi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The lag or the intersession interval (ISI) is the gap between two learning sessions. Lag effects are one of those effects that few studies have examined. Moreover, albeit a huge bulk of research on input spacing (i.e., phenomenon of distributed learning conditions) has been done in laboratory setting, few studies have directly examined this issue within real contexts. Therefore, the purpose of this study was to examine the impact of not only spaced-short but also spaced-long condition on the vocabulary knowledge of EFL learners. To achieve this goal, 37 intermediate level EFL learners were selected from four intact classes. The whole process took place in nine weeks; two testing sessions for pretest and a 28-day delayed posttest, two learning sessions and a final review session. Learning was done in two sessions. In this process, 20 target items were divided into 10 target words from each two lists. The first 10 words were studied during the first session, and reviewed during the review session. Eight days (intersession interval) ISI was specified for the spaced-long condition. Finally, a 1-day ISI was specified for the spaced-short condition. To do so, the second 10 words during the second session were studied, and then they were reviewed during the review session. The results of paired samples t-test revealed that spaced-long input was more effective than the space-short. Spaced-long condition could help learners for conceptual understanding to develop, reduce forgetting and provide opportunities for learners to learn more efficiently.